Examining Patient Feedback and the Role of Cognitive Arousal in Treatment Non-response to Digital Cognitive-behavioral Therapy for Insomnia during Pregnancy. Issue 2 (4th March 2022) - Kalmbach, David A.; Cheng, Philip; Roth, Thomas; Swanson, Leslie M; Cuamatzi-Castelan, Andrea; Roth, Andrea; Drake, Christopher L
ABSTRACT: Objective: Insomnia affects over half of pregnant and postpartum women. Early evidence indicates that cognitive-behavioral therapy for insomnia (CBTI) improves maternal sleep and mood. However, standard CBTI may be less efficacious in perinatal women than the broader insomnia population. This study sought to identify patient characteristics in a perinatal sample associated with poor response to CBTI, and characterize patient feedback to identify areas of insomnia therapy to tailor for the perinatal experience. Participants: Secondary analysis of 46 pregnant women with insomnia symptoms who were treated with digital CBTI in a randomized controlled trial. Methods: We assessed insomnia, cognitive arousal, and depression before and after prenatal treatment, then 6 weeks postpartum. Patients provided feedback on digital CBTI. Results: Residual cognitive arousal after treatment was the most robust factor associated with treatment non-response. Critically, CBTI responders and non-responders differed on no other sociodemographic or pretreatment metrics. After childbirth, short sleep (<6 hrs/night) was associated with maternal reports of poor infant sleep quality. Patient feedback indicated that most patients preferred online treatment to in-person treatment. Although women described digital CBTI as convenient and helpful, many patients indicated that insomnia therapy would be improved if it addressed sleep challenges unique to pregnancy and postpartum. Patients requested education on maternal and infant sleep, flexibility in behavioral sleep strategies, and guidance to manage infant sleep. Conclusions: Modifying insomnia therapy to better alleviate refractory cognitive arousal and address the changing needs of women as they progress through pregnancy and early parenting may increase efficacy for perinatal insomnia. Name: Insomnia and Rumination in Late Pregnancy and the Risk for Postpartum Depression URL: clinicaltrials.gov Registration: NCT03596879